(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2014)
In the administration of estates in Malaysia, the bone of contention is the determination of the extent and types of property that shall be regarded as the deceased’s estate before it can be distributed to the rightful legal heirs. In many instances, claims have been made by the interested party for a particular property to be excluded from the list of the deceased’s estates and should not be subject to such distribution. This article seeks to examine the extent and types of property left by the deceased that are considered as estates which warrant distribution accordingly. The discussion focuses on the issues of joint accounts, nominated estates, derivative pension and ex-gratia, which have always been the subject of disputes on whether such properties should form part of the deceased’s estates or not. Relevant statutory provisions and decided cases on these issues are analysed and propounded accordingly to elucidate the position of such properties in the deceased’s estates. This article sums up that there is a need for specific statutory provisions to precisely clarify with respect to what is considered as the deceased’s estate. Keywords: Muslim deceased’s estate, joint accounts, nominated estates, pension, ex-gratia, Malaysia, Syariah court